DIVERSITY AND POPULATION DYNAMICS OF ENTOMOFAUNA OF TWO DIVERGE AGRO-ECOSYSTEMS IN THE THAR DESERT - SAIGA, DEEPAK; SRIVASTAVA, MEERA; SAXENA, M. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
During the present investigation the diversity and population dynamics of entomofauna of two diverge agro-ecosystems viz. sewage-irrigated and well water irrigated fields, in arid region of Rajasthan were carried out during different seasons. In all, insects belonging to five orders (Coleoptera, Hemiptera, Lepidoptera, Orthoptera, Dermaptera) represented by 46 genera were recorded. Variations in the diversity and population of insect fauna was observed which was perhaps because of difference in crop sown and microclimatic conditions during the particular period.